(untitled) (Theatrum historiae, 2010)
Concepts such as money and wealth in general changed greatly in the Middle Ages. On the one hand the medieval world was permeated with the simple ideas of the barbarians, who plainly identified wealth with happiness and success. Yet on the other hand ideas began to appear and spread which were drawn from the legacy of antiquity and which judged money according to the positive and negative effect it had on society. Medieval culture was multifaceted and varied greatly from territory to territory. In this culture money could be seen on several levels. One of the most comprehensive looks at money in the culture of the Middle Ages was given by Ryszard Kiersnowski, whose work became an inspiration for later researchers. Christianity had a positive relationship towards money, and the first Christians accepted it as a normal part of life. Money at that time served as a kind of medium, the images on which disseminated a substantial ideology in society, which succumbed to the power of these images. Therefore, first of all we need to go into the iconography of medieval coins, which can be divided up into two groups – the ecclesiastical and the secular, which in many cases obviously overlap and supplement one another (F. Friedens- burg). The Church’s mission to spread harmony in the Middle Ages evidently created the idea that money could become a means to allow the Christian to help the poor and power- less. This tendency can also be seen in the pictures on the coins; the coin imagery, by showing good deeds, was supposed to educate people to use the money to perform good deeds themselves. This began with the establishment of pawn shops, which helped town- dwellers out of financial difficulties. The first municipal – i.e. public – pawn shop was apparently set up in Perugia in 1462 (Monte dei Poveri). In Papal Rome, after approval had been granted by the Pope in 1515, this led to the creation of an institution – Monte di Pieta, which was a precursor to the people’s banking institutions that would come later. Some pawn shops did not charge any interest, but most took the opportunity to do so. Clearly we should also point out that these charitable institutions later became standard commercial financial institutions. In the Middle Ages money-lending with interest was widespread. Usury, however, was officially prohibited and it was hard to get around this ban. Yet the effort to satisfy the surviving kin of money-lenders was so powerful that it gave rise to teaching about purgatory. The souls of money-lenders in purgatory could be helped if their surviving family members devoted themselves to pious deeds. According to J. Le Goff, teaching about purgatory could have been of great significance, as the fact that purgatory showed mercy even to money-lenders was one factor in the rise of capitalism. Purgatory became a form of hope for certain types of sinners who could not otherwise redeem themselves of their sins, but also for following certain professions which formerly led to damnation. Obviously teaching about purgatory was a somewhat uncertain course of action and when theological speculations about how to weaken the ban on usury failed, people looked for other ways to circumvent the prohibition. Sometimes a loan was disguised as a gift, to which the debtor responded with a gift that was worth more than the sum originally loaned. Other ways of getting round the ban involved a variety of sham purchases and sales. In the 15th century people thought it necessary to differentiate between illegitimate loans and “legitimate” loans; cases were generally judged according to the amount of interest. Opinions evidently differed, and eventually diet decrees set the legal rate of interest. In 1484 the Bohemian diet (Landtag) set the maximum permissible interest rate at 10 percent, which was later reduced to 6 percent. The church authorities protested against this, but with no great success. It is interesting to observe opinions concerning money-lending changed in the Unity of the Brethren. This began with the opinions of Petr Chelčický, which were in line with his radically anti-usury view of society. Later, however, the Unity of the Brethren took a less harsh stance on the issue. Medieval man was accompanied by money from the cradle, as a christening gift, to the grave, as the obol of the dead. From the first instance to the latter he used coins every day of his life, often without noticing how the money was actually using him.